2013
DOI: 10.1515/polyeng-2012-0122
|View full text |Cite
|
Sign up to set email alerts
|

Molecular iodine/polymer complexes

Abstract: A unique feature of molecular iodine by far, is its ability to bind to polymeric materials. A plethora of natural and synthetic polymers develop complexes when treated with molecular iodine, or with a mixture of mole cular iodine and potassium iodide. Many unexpected findings have been encountered upon complexation of iodine and the polymer skeleton, including the color formation, the polymer morphology changes, the compl exation sites or regions, the biological activity, and the electrical conductivity enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
127
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 162 publications
(150 citation statements)
references
References 330 publications
(396 reference statements)
3
127
0
5
Order By: Relevance
“…24−29 Iodine is known to form charge transfer complexes (CTCs) with electron-rich molecules such as those with lone pairs and aromatic rings in the form of polyiodides. 29,30 Bromine is another halogen that has been studied for enhancement of the carbonization process and has been compared with iodine. 26,31 It was found that bromination is nonselective and localized, while iodination was selective to aromatics and nonlocalized, iodinating throughout the material.…”
Section: ■ Introductionmentioning
confidence: 99%
“…24−29 Iodine is known to form charge transfer complexes (CTCs) with electron-rich molecules such as those with lone pairs and aromatic rings in the form of polyiodides. 29,30 Bromine is another halogen that has been studied for enhancement of the carbonization process and has been compared with iodine. 26,31 It was found that bromination is nonselective and localized, while iodination was selective to aromatics and nonlocalized, iodinating throughout the material.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Instead, molecular iodine has been mostly and intensively employed as dopant for polymers, generating iodine-polymers' complexes. [14] Recently, a fascinating finding lies on the reaction of submicron-sized polymer particles (PSE) containing imidazoline selenones with halogens to form adducts with vivid color change from white to red-orange (red-orange with I 2 , yellow with Br 2 , and yellow with faint red color with Cl 2 ). [15] In this review paper, an account of uses of molecular iodine in polymer synthesis is outlined.…”
Section: Introductionmentioning
confidence: 99%
“…The binding energy at 620.65 and 632.15 eV is associated with CI bond in the I 3d spectrum (Figure C), and other valence states of iodine, such as I − (3d 5/2 , 618 eV), IO 3− (3d 5/2 , 623 eV), and I 2 (3d 5/2 , 619.9 eV) were not detected in the XPS spectrum . Moreover, the binding energy at 285.4 eV in the C 1s spectrum further confirmed the formation of CI bond (Figure D), and the starch‐I 2 colorimetric reaction and AgNO 3 ‐I − precipitation reaction revealed the absence of I − or I 2 in the as‐prepared I‐PPy nanoparticles (Figure S1A, Supporting Information). These results demonstrated that iodine was covalently bound to the C atom in the form of CI bond in I‐PPy nanoparticles.…”
Section: Resultsmentioning
confidence: 71%